AN EFFICIENT METHOD FOR RURAL ELECTRIFICATION GRID DESIGN - Nyakudya, R.; Mhlanga, S. (European Scientific Journal, ESJ, 2014)
This paper investigates the optimization of the electricity grid network in rural community of Chegutu district, in Zimbabwe. The Kruskal’s algorithm is used for the minimum spanning tree to carry out the optimization process.The project seeks to find how a network with a number of possible connections can have the least possible distance. The main objective of the optimization procedure is to minimize the total distance of the network connections, so as to minimize resources that are used when carrying out projects. Rural Electrification Agency has been failing to meet their targets for extension of the electricity grid network because of shortage of resources and input capital, thus the researcher adopts the idea of network optimization as a way of saving resources so that they can be used for other projects. The researcher used the algorithm to carry out the manual computation of the optimization process and also used C sharp programming language to create a code that is able to minimize the total distance of the network. In this dissertation the Kruskal’s algorithm has been translated into a simple model that can be easily used to map distances between nodes and vertices. The model presented in this dissertation help network service providers such as electricity, telephone and information technology to optimize their network resources so as to save money and resources for other uses in the future. The optimisation process shows that a total of 74km of 11kV power line could be saved from the network.